2021
DOI: 10.1111/anu.13380
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lipid level on the growth and reproductive performance of female orange mud crab, Scylla olivacea (Herbst, 1796), during the fattening period

Abstract: Mud crab genus Scylla belongs to the family Portunidae, is commonly associated with the mangrove wetlands and is grown well in the muddy habitats subjected to tidal changes. Compared with other portunid species, mud crab genus Scylla grows faster and attains larger size over a short period (Viswanathan & Raffi, 2015). This species signifies a highly valued candidate for coastal fisheries with a high price in the export market owing to their high nutritional value and delicious taste. There are four species of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…From the proximate analysis, it is noticed that the lipid levels in diets are increased by increasing the level of fish oil, which subsequently resulted in a higher level of HUFA, particularly ARA, EPA, and DHA. Reportedly, Aaqillah-Amr et al [26,47] documented an increase in ARA, EPA, and DHA in the diets developed for S. olivacea broodstock fed with 120 g/kg lipids (ARA = 0:81 mg/g, EPA = 1:27 mg/g, and DHA = 1:20 mg/g) as compared to that fed with 60 g/kg lipids (ARA = 0:47 mg/g, EPA = 0:32 mg/g, and DHA = 0:26 mg/g). These findings indicated that the increase in HUFA contents increased the lipid level of the crustacean diets, which is important when it comes to signaling pathways and growth performance of decapod crustaceans [49].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the proximate analysis, it is noticed that the lipid levels in diets are increased by increasing the level of fish oil, which subsequently resulted in a higher level of HUFA, particularly ARA, EPA, and DHA. Reportedly, Aaqillah-Amr et al [26,47] documented an increase in ARA, EPA, and DHA in the diets developed for S. olivacea broodstock fed with 120 g/kg lipids (ARA = 0:81 mg/g, EPA = 1:27 mg/g, and DHA = 1:20 mg/g) as compared to that fed with 60 g/kg lipids (ARA = 0:47 mg/g, EPA = 0:32 mg/g, and DHA = 0:26 mg/g). These findings indicated that the increase in HUFA contents increased the lipid level of the crustacean diets, which is important when it comes to signaling pathways and growth performance of decapod crustaceans [49].…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on the ovarian and hepatopancreatic lipid concentration during reproduction have been extensively reported in several crustacean species studies such as red claw crayfish, Cherax quadricarinatus [44]; mud crab, Scylla olivacea [45]; and mantis shrimp, Oratosquilla oratoria [46]. It is widely accepted that lipid levels in crustaceans increase with their maturation stages [47]. In many cases, the ovarian lipid concentration increased during the reproductive phases, while the lipid content in the hepatopancreas significantly decreased [44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…The fattening period varies according to the condition of the crab habitat and food quality. It has been shown that brackish water is most favorable for shortening the fattening period of around 30 days [191]. This information explains how minerals, temperature, and salinity play a key role in the shell hardening and survival of larval stages (Figure 9).…”
Section: Habitat Water Quality Management and Techniques To Enhance M...mentioning
confidence: 90%